FAKTOR PENGHAMBAT DAN PENDUKUNG IMPLEMENTASI CONTINUOUS QUALITY IMPROVEMENT DALAM PELAYANAN KEPERAWATAN: SCOPING REVIEW - Ahmadi Ahmadi; Mei Lestari Ika Widyyati (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2026)
Background: Continuous Quality Improvement (CQI) is a systematic approach that has been increasingly adopted in nursing services to improve the quality of patient care. Although CQI implementation has advanced considerably, a comprehensive understanding of the barriers and facilitators influencing its implementation in nursing practice remains limited. This scoping review aimed to comprehensively map and analyze the barriers and facilitators to CQI implementation in nursing services. Objective: To identify the barriers and facilitators to the implementation of Continuous Quality Improvement in nursing services. Methods: This scoping review was conducted following the Arksey and O'Malley framework. A systematic literature search was performed in PubMed, Scopus, and Web of Science databases. A mixed-methods approach, incorporating content analysis and narrative synthesis, was used to summarize the findings. The review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). Results: A total of 20 studies were included in the final review. The main barriers were categorized into four dimensions: (1) limitations in human resources, financial resources, and infrastructure; (2) organizational challenges, including limited leadership engagement and high staff turnover; (3) gaps in knowledge and training; and (4) technical and logistical issues. The key facilitators included strong leadership and organizational support, effective teamwork and collaboration, education and capacity building, implementation adaptability, and the use of technology and supportive systems. Conclusion: The implementation of CQI in nursing services requires a multidimensional approach that addresses individual, organizational, and health system factors. Context-specific implementation strategies, strengthened nursing leadership, continuous education and training, and the effective utilization of technology are critical to achieving the sustainable implementation of CQI and improving the quality of nursing care.